Strategi Guru Mengatasi Kesulitan Belajar Siswa Terindikasi Disleksia - Astuti, Nadya (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2023)
This research has a background where students experience reading difficulties in class III. This research aims to This research is based on the problems of students who experience reading difficulties in class III. This research aims to determine teachers' strategies for dealing with students' learning difficulties as indicated by descriptive research. Data collection uses observation, interview and documentation techniques. There are two sources of data in this research, namely primary and secondary. Primary data sources are three students and one homeroom teacher. Secondary data sources are interview transcripts and photographs. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this research show the class teacher's strategy in dealing with students' difficulties in learning to read by providing additional hours for students who cannot read by using an individual approach. In this way the teacher can interact directly with students who have difficulty reading, in this case the teacher always pays attention to the students. one student with another in the hope that the strategy used is successful or not. It can be concluded that teachers must prepare more interesting strategies so that students are interested in learning in the classroom and outside the classroom. Teachers must have the competence to recognize, understand the characteristics and needs of students.